The Tramp Is Back - McCallum, Todd (Labour / Le Travail, 2005)
The article reviews and comments on "The Tramp in America" by Tim Creswell, "Citizen Hobo: How a Century of Homelessness Shaped America" by Todd DePastino, and "Indispensable Outcasts: Hobo Workers and Community in the American Midwest, 1880-1930" by Frank Tobias Higbie.